Determining the identity of the place through spatial and landscape analysis. A case study of the former town of Wieniawa in Lublin - Jabłoński, Wojciech (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
The article presents a spatial and landscape analysis of the area of the former town of Wieniawa in Lublin, on the basis of which the features of the local anthropological landscape were specified. As part of the work, a number of analyzes were performed in 2022, including: scenic, historical, cubature, development, planning documents and administrative decisions. On their basis, an attempt was made to determine the identity of the place of the analyzed area.